1996
DOI: 10.1007/bf02174382
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of the cultivated mushroom,Agaricus bisporus, to hygromycin B resistance

Abstract: Application of biotechnology to the cultivated mushroom, Agaricus bisporus, has been hampered thus far by the lack of a transformation system. Here, transformation of both a homo- and a heterokaryotic strain of A. bisporus to hygromycin B resistance is described. Transforming DNA was integrated into the A. bisporus genome and stably maintained throughout vegetative growth. Transformants of the heterokaryotic strain formed transgenic fruiting bodies. Promoters derived from the unrelated ascomycete Aspergillus n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 26 publications
2
43
0
Order By: Relevance
“…As the dominant selectable marker gene hph has previously been successfully employed to develop hygromycin resistancebased transformation systems for basidiomycete species, such as the edible mushrooms A. bisporus and P. ostreatus and the model systems C. cinerea and S. commune (10,27,35,42,55), we used the same gene to establish transformation systems of C. passeckerianus. We were successful in generating hygromycin-resistant transformants by using both Agrobacterium-and PEG-mediated methods.…”
Section: Vol 75 2009 Genetic Transformation Of Clitopilus Passeckermentioning
confidence: 99%
See 1 more Smart Citation
“…As the dominant selectable marker gene hph has previously been successfully employed to develop hygromycin resistancebased transformation systems for basidiomycete species, such as the edible mushrooms A. bisporus and P. ostreatus and the model systems C. cinerea and S. commune (10,27,35,42,55), we used the same gene to establish transformation systems of C. passeckerianus. We were successful in generating hygromycin-resistant transformants by using both Agrobacterium-and PEG-mediated methods.…”
Section: Vol 75 2009 Genetic Transformation Of Clitopilus Passeckermentioning
confidence: 99%
“…Vectors containing the Escherichia coli hph gene (for hygromycin resistance) coupled with PEG-mediated and/or Agrobacterium-mediated transformation systems have previously been developed for a few basidiomycete species, mainly model systems such as Coprinopsis cinerea (10) and Schizophyllum commune (35,51), or edible fungi, including Agaricus bisporus (55), Lentinula edodes (50), and Pleurotus ostreatus (42). Phleomycin resistance vectors were also employed to transform C. cinerea (27), S. commune (52), and Trametes versicolor (1).…”
mentioning
confidence: 99%
“…Pleurotus ostreatus [5][6][7] and Agaricus bisporus 8) have been transformed by PEG/CaCl 2 . Protoplasts of Agrocybe aegerita prototrophs have been transformed to prototrophy by electroporation with transformation frequencies ranging from 1 to 26 transformants/mg of DNA.…”
Section: )mentioning
confidence: 99%
“…In U. maydis, the linearization of the vector pHL1 increased the transformation frequency by about 20 times (34), and studies into other fungi, such as A. bisporus, M. grisea, and S. cerevisae have reported the same observation (14,24,31). Whitehead et al (35) showed that the use of the linearized vector pSTA10, which carries the A. niger niaD gene, increased the transformation frequency from 6.2 to 13.3 transformants/μg DNA.…”
Section: Transformationmentioning
confidence: 93%